Calcium Signaling Protocols - Lambert, David G.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2005)
Now extensively updated and expanded, Calcium Signaling Protocols, Second Edition continues the excellence of the highly regarded first edition. New to this edition are chapters on the electrophysiological measurement of Ca2+ channel activity, enhanced coverage of confocal microscopy, and practical tutorials on two of the most common industrial high-throughput machines, the Fluorometric Imaging Plate Reader (FLIPR), and the FlexStation. All experimental chapters provide readily reproducible techniques for measuring the many facets of Ca2+ signaling. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Authoritative and up-to-date, Calcium Signaling Protocols, Second Edition provides for novice and expert researchers alike both theoretical and practical information for the optimal design and performance of studies of intracellular Ca2+ regulation.
General -- Fluorescent Measurement of [Ca2+]c -- Measurement of [Ca2+]i in Whole Cell Suspensions Using Fura-2 -- Measurement of [Ca2+]i in Cell Suspensions Using Indo-1 -- Specialist Measurement Systems -- Confocal Microscopy -- Single-Cell and Subcellular Measurement of Intracellular Ca2+ Concentration -- Ratiometric Ca2+ Measurements Using the FlexStation® Scanning Fluorometer -- Measuring Ca2+ Changes in Multiwell Format Using the Fluorometric Imaging Plate Reader -- Measurement of Ca2+ Channel Activity -- Measurement of Ca2+ Entry Using 45Ca2+ -- Measurement of [3H]PN200-110 and [125I]?-Conotoxin MVIIA Binding -- Whole-Cell Patch Clamp Recording of Voltage-Sensitive Ca2+ Channel Currents -- Measurement of Ins(1,4,5,)P3 and Ca2+ Release From Intracellular Stores -- Measurement of Phospholipase C by Monitoring Inositol Phosphates Using [3H]Inositol-Labeling Protocols in Permeabilized Cells -- Measurement of Inositol(1,4,5)Trisphosphate Using a Stereospecific Radioreceptor Mass Assay -- Measurement of Calcium Fluxes in Permeabilized Cells Using a 45Ca2+ Uptake and Release Assay -- Microinjection of myo-Inositol(1,4,5)Trisphosphate and Other Calcium-Mobilizing Agents Into Intact Adherent Cells -- Measurement of Free [Ca2+] Changes in Agonist-Sensitive Internal Stores Using Compartmentalized Fluorescent Indicators -- Specialist Measurement Techniques -- Measurement of [Ca2+]i in Smooth Muscle Strips Using Front-Surface Fluorimetry -- Measurement of Calcium and Movement in Heart Cells -- Simultaneous Analysis of Intracellular pH and Ca2+ From Cell Populations -- Measurement of Cytosolic-Free Ca2+ in Plant Tissue -- Ca2+-Sensitive Targets -- Assay and Purification of Calmodulin-Dependent Protein Kinase -- Assay and Purification of Calmodulin-Dependent Cyclic Nucleotide Phosphodiesterase and Isozyme Separation -- Measurement of Ca2+-ATPase Activity (in PMCA and SERCA1).
Keywords: Biochemistry; Biochemistry, general